Predictors of successful endovascular recanalization in patients with symptomatic nonacute intracranial large artery occlusion - Shuo Yan; Hao Feng; Lin Ma; Ji-Chong Xu; Hong-Jie Han; Hong-En Huang; Hua-Qiao Tan; Chun Fang (BMC Neurology, 2023)
Abstract Background Endovascular recanalization in patients with symptomatic nonacute intracranial large artery occlusion (ILAO) has been reported to be feasible, but technically challenging. This study aimed to determine the predictors of successful endovascular recanalization in patients with symptomatic nonacute ILAO. Methods The outcomes of endovascular recanalization attempts performed in 70 consecutive patients showing symptomatic nonacute ILAO with hemodynamic cerebral ischemia between January 2016 to December 2022 were reviewed. Potential variables, including clinical and radiological characteristics related to technical success, were collected. Univariate analysis and multivariate logistic regression were performed to identify predictors of successful recanalization for nonacute ILAO. Results Technically successful recanalization was achieved in 57 patients (81.4%). The periprocedural complication rate was 21.4% (15 of 70), and the overall 30-day morbidity and mortality rates were 7.1% (5 of 70) and 2.9% (2 of 70), respectively. Univariate analysis showed that successful recanalization was associated with occlusion duration, stump morphology, occlusion length, slow distal antegrade flow sign, and the presence of bridging collateral vessels. Multivariate analysis showed that occlusion duration ≤ 3 months (odds ratio [OR]: 22.529; 95% confidence interval [CI]: 1.636-310.141), tapered stump (OR: 7.498; 95% CI: 1.533–36.671), and occlusion length < 10 mm (OR: 7.049; 95% CI: 1.402–35.441) were independent predictive factors for technical success of recanalization. Conclusions Occlusion duration ≤ 3 months, tapered stump, and occlusion length < 10 mm were independent positive predictors of technical success of endovascular recanalization for symptomatic nonacute ILAO. These findings may help predict the likelihood of successful recanalization in patients with symptomatic nonacute ILAO and also provide a reference for the selection of appropriate patients. Further prospective and multicenter studies are required to validate our findings.